FAKTOR DOMINAN PEMICU KEJADIAN PLEBITIS DI RS SWASTA KOTA KUPANG - Yustina Kristianingsih; Dominggus Ruku Yudit Pramono; Yunita Wiguna (Jurnal Keperawatan Malang, 2025)
Background: Phlebitis is a type of HAI infection that is acquired by patients when hospitalized and is followed by clinical manifestations that appear at least 3 x 24 hours. Most of the patients treated in hospital have IVs installed, and phlebitis still often occurs even though the process of installing the infusion has been done correctly and using aseptic technique. Phlebitis is caused by several factors such as age, gender, BMI, type of fluid and others. Objective: to find out the factors that influence the occurrence of phlebitis Method: This research uses a descriptive analytical design. The population of this study were all patients treated in the adult inpatient ward of a private hospital in the city of Kupang. Sample collection was carried out by consecutive sampling with a total of 58 respondents who met the inclusion criteria. Data was collected using an observation sheet for the factors gender, age, BMI, type of infusion fluid and an observation sheet for the incidence of phlebitis. Data analysis to determine the dominant factors that influence the incidence of phlebitis using simple regression Results: research results obtained: factors that influence the incidence of phlebitis in Kupang city private hospitals are the type of fluid Implications: It is important to increase monitoring in patients receiving hypertonic fluid therapy to prevent phlebitis. And for patients who receive hypertonic fluid therapy, it is important to analyze the relationship between the type and size of IV catheter, vein condition, location and fluid placement time. Keywords: fluid, dominant factor, phlebitis